Perancangan Usaha Pemanfaatan Limbah Kulit Pepaya Menjadi Produk Papain untuk Pelembut Daging - Hakim, Budi Lukman; Taptajani, Dedi Sa'dudin; Ferdiansyah, Riki (Institut Teknologi Garut, 2023)
MSMEs in Indonesia have a significant contribution to GDP, with papaya skin being one of the innovations in the MSME sector as a meat tenderizer. This research was carried out in an analysis of company design in terms of the feasibility aspect of processing papaya skin into papain products, based on literature that shows the effectiveness of papain as a meat softener. Papaya skin waste which contains papain can be made into flour and does not change its role in softening the flesh. The method of making it is through a drying process and is not too complicated so it can be an effective method and apart from that, the raw material for papaya skin waste is easy to obtain by utilizing the waste. produced from a sweets factory made from young papaya in Garut. Based on this, research was carried out to design a business for utilizing papaya skin waste for meat softening and to determine the feasibility aspect. The results show that papain products produced from 100% papaya skin meet the expected criteria. The market aspect in Garut Regency shows promising business potential considering the market demand for meat income to the Garut Regency market is 224.66 tons/year with the need for meat softener papain products estimated at 748,866 kg/month. The technical aspects in processing papain products using the drying method and the evaluation of financial aspects through calculating material costs, investment, COGS, BEP, PP, IRR and ROI confirm that this business is feasible to run with significant growth opportunities in the future.